Dietary Patterns in Pregnancy and Biomarkers of Oxidative Stress in Mothers and Offspring: The NELA Birth Cohort - Morales, Eva; García-Serna, Azahara M.; Larqué, Elvira; Sánchez-Campillo, María; Serrano-Munera, Ana; Martinez-Graciá, Carmen; Santaella-Pascual, Marina; Suárez-Martínez, Clara; Vioque, Jesús; Noguera-Velasco, José A.; Avilés-Plaza, Francisco V.; Martínez-Villanueva, Miriam; et al. (Frontiers in Nutrition, 2022)
Background: Although adherence to Mediterranean and antioxidant-rich diets during pregnancy is suggested to improve maternal-fetal health by reducing oxidative stress, no study is available yet. Objective: We examined whether maternal dietary patterns in pregnancy impact biomarkers of oxidative stress in mothers and their offspring. Methods: Study population included 642 mothers and 335 newborns of the “Nutrition in Early Life and Asthma” (NELA) birth cohort. Maternal diet during pregnancy was assessed by a validated food frequency questionnaire and a priori-defined dietary indices (rMED, aMED, DASH, AHEI and AHEI-2010) were calculated. Biomarkers measured were: hydroperoxides, carbonyl groups and 8-hydroxydeoxyguanosine (8OHdG) determined in maternal blood and newborn cord blood, and urinary maternal and offspring 15-F2t-isoprostane. Multivariate linear regression models were performed. Results: Maternal rMED score was inversely associated with maternal levels of 8OHdG at mid-pregnancy (beta per 1-point increase = -1.61; 95% CI -2.82, -0.39) and newborn levels of hydroperoxides (beta per 1-point increase = -4.54; 95% CI -9.32, 0.25). High versus low maternal rMED score was marginally associated with decreased levels of 8OHdG in newborns (beta = -9.17; 95% CI -19.9, 1.63; p for trend 0.079). Maternal DASH score tended to be inversely associated with maternal urinary 15-F2t-isoprostane (beta per 1-point increase = -0.69; 95% CI, -1.44, 0.06). High versus low maternal AHEI score was associated with reduced offspring urinary levels of 15-F2t-isoprostane (beta = -20.2; 95% CI -38.0, -2.46; p for trend 0.026). Conclusion: These results suggest that maternal adherence to healthy dietary patterns during pregnancy may reduce DNA damage and lipid oxidation in mothers and offspring.